Attacking the King's English Implications for Journalism Arising from Feminist Critiques of Public Language - Ward, Jean W. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
Feminist resentment of journalistic language use can be found in published letters to the editor, in feminist periodicals, and in public address. This paper examines commentary on language, noting the charge that journalistic language frequently is discriminatory and offensive to women in defining them, in designating their identity, and in revealing the assumption that "all people are male unless proven female." The implications for journalism practice and research which arise from feminist language critiques include: (1) the need in journalism to consider linguistic perspectives, (2) the possibility that language change will be accomplished deliberately, (3) the consideration of journalistic language from the viewpoints of language both as director and as reflector of social change, (4) the possibility that journalistic language use produces covert signals which reduce potential audiences and inhibit opinion formation, and (5) the challenge which faces journalism educators in teaching women students and in preparing all students to understand relationships between social change and language change and the mediating role played by journalism in public dialogue. (Author)
ERIC Note: Paper presented at the Annual Meeting of the Association for Education in Journalism (57th, San Diego, California, August 18-21, 1974).
Microfiche.
Keywords: College Instruction; Speeches/Meeting Papers